Effects of Different Doses of Eucalyptus Oil From Eucalyptus globulus Labill on Respiratory Tract Immunity and Immune Function in Healthy Rats - Shao, Jie; Yin, Zhenjie; Wang, Yaqin; Yang, Yudong; Tang, Qing; Zhang, Mingming; Jiao, Jieying; Liu, Chengjie; Yang, Mingfang; Zhen, Lifang; Hassouna, Amira; White, William Lindsey; et al. (Frontiers in Pharmacology, 2020)
Eucalyptol (1,8-cineole), the major constituent of eucalyptus oil (EO), was used in traditional medicine as a remedy for colds and bronchitis. This study aimed at clarifying the effect of eucalyptol on respiratory immune function of CD8 and CD4 cells, and alveolar macrophages (AM). Thirty male Sprague-Dawley rats were divided into experimental and control groups. The drug was given once a day for 3 weeks and the experimental group was divided according to the eucalyptol dose into: 30, 100, and 300 mg·kg-1 groups. Flow cytometry was used to detect the phagocytic function of CD4, CD8 cells and AM in the bronchopulmonary lavage fluid. The 30 and 100 mg·kg-1 groups had an up-regulation effect on CD8 (p<0.05), with no significant effect on macrophage phagocytosis. The 300 mg·kg-1 group had an inhibitory effect on CD8 and macrophage phagocytosis (p<0.05), with no significant difference in CD4 between groups. Further investigation was conducted to evaluate the effect of EO on immune function in rats by detecting blood T, B and NK cells using flow cytometry, and blood IgA, IgG, IgM and IFN-γ levels by ELISA. High dosage of eucalyptol significantly reduced the proportion of blood B and NK cells (p<0.05). IgA was decreased in the 100 and 300 mg·kg-1 groups (p<0.05). There are no significant differences between the number of T cells and the IgG, IgM and IFN-γ levels between experimental and control groups. Rational use of EO containing eucalyptol can improve the immune function of the respiratory tract and the body immunity, while high dose could have damaging effects, through modifying the phagocytic function of CD8 cells and reducing the proportion of blood B cells, NK cells and IgA.